Réponses

2014-05-03T16:12:35+02:00
Bonjour,

Tu peux procéder comme pour tout autre système. Par substitution, par exemple.
\begin{cases}x \sqrt{2} +y=5\\
 x-y \sqrt{2}=0 \end{cases}\\
\begin{cases}x \sqrt{2} +y=5\\
 x=y \sqrt{2} \end{cases}\\
\begin{cases}y\sqrt 2 \times  \sqrt{2} +y=5\\
 x=y \sqrt{2} \end{cases}\\
\begin{cases}3y=5\\
 x=y \sqrt{2} \end{cases}\\
\begin{cases}y = \frac 53\\
 x=y \sqrt{2} = \frac{5\sqrt 2}{3} \end{cases}\\
S = \left\{\left(\frac 53 ; \frac{5\sqrt 2}{3}\right) \right\}

Si tu as des questions, n'hésite pas ! =)